(untitled) (Materiali di Estetica. Terza serie, 2016)
The article introduces Guido Davide Neri’s archive, given to the Philosophy Library of The University of Milan by his heirs, shortly summing up the subject, processing steps from the bibliographical and archival treatment point of view, as well as promotion and enhancement initiatives